Why do we err? : representational and processing factors of judgment and decision making - Leitão, Maria Adelaide Silva, 1970- (2014)
Tese de mestrado, Ciência Cognitiva, Universidade de Lisboa, Faculdade de Psicologia, Faculdade de Ciências, Faculdade de Medicina, Faculdade de Letras, 2014